Application of Role Playing Learning Model To Improve Science Learning Outcomes - Lamiada, Lamiada (Journal of Teaching and Education, 2022)
Low science learning outcomes remain a challenge in elementary education, particularly when learning activities are dominated by teacher-centered instruction. This study was motivated by the low average science achievement of Grade VI students at SD Negeri 66 Mambo, which was recorded at 67.14. To address this issue, the study implemented the role-playing learning model as an alternative instructional strategy to improve students’ science learning outcomes.  This research employed Classroom Action Research (CAR) consisting of two cycles. Data were collected through observation sheets to measure teacher and student activities and achievement tests to assess students’ learning outcomes. The findings indicate a significant improvement in both learning processes and outcomes following the implementation of the role-playing model. Teacher activity increased from an average of 62.5% in Cycle I to 85.25% in Cycle II. Similarly, student activity showed a notable improvement, rising from 50% in Cycle I to 83.3% in Cycle II. Regarding learning outcomes, the initial average class score of 67.14 with a learning completeness percentage of 50% increased to 75.17 in Cycle I, representing an improvement of 11.96% and a mastery percentage of 57.14%. Further improvement was observed in Cycle II, with the class average score increasing to 87.85, a learning outcome improvement of 30.84%, and 85.71% of students achieving mastery.  These results demonstrate that the role-playing learning model is effective in enhancing student engagement and improving science learning outcomes. This study provides practical pedagogical